Detection of virulence factors in opportunistic bacteria: advances, challenges, and practical implementation - Chebotar, Igor; Azizov, Ilya; Edelstein, Mikhail; Kozlov, Roman (Frontiers in Microbiology, 2025)
Virulence is a property of bacteria that determines the degree of damage inflicted on humans. In modern medicine, there is an underestimation of the importance of testing the virulence of opportunistic pathogens to assess prognosis, optimize therapy, and evaluate the risk of developing probable complications of the infectious process. This review analyzes the basic characteristics of virulence, including multifactoriality, complex regulation, its relationship with fitness and bet-hedging in the context of choosing optimal methods for quantitative virulence testing. The possibilities of various methodological approaches for evaluation of virulence in clinical laboratory settings are considered. Current technology levels allow laboratories to be equipped with test systems for implementing methods to detect the virulence of clinical opportunistic isolates. At the hospital level, determining the virulence of isolates from individual patients will improve the prediction of the course of the infectious process and help to rationalize infection control based on principles similar to those used in combating antibiotic-resistant strains. Knowledge of virulence properties of relevant pathogen clones is required for the successful development of anti-virulence strategies.